2017
DOI: 10.1111/liv.13371
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from cirrhosis and hepatocellular carcinoma in Western Europe over the last 40 years

Abstract: The LC mortality rate is decreasing in Europe, yet there is a significant increase in HCC mortality. This phenomenon requires greater attention so we can understand the risk factors and implement preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 48 publications
1
32
1
2
Order By: Relevance
“…Therefore, it is possible that the burden of mortality in ESLD shifted from in‐hospital to the early post‐discharge period . Several studies from Europe and Australia have confirmed a marked reduction of in‐hospital mortality among patients with cirrhosis, but without assessment of mortality rates in the outpatient setting following the discharge from the hospital …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that the burden of mortality in ESLD shifted from in‐hospital to the early post‐discharge period . Several studies from Europe and Australia have confirmed a marked reduction of in‐hospital mortality among patients with cirrhosis, but without assessment of mortality rates in the outpatient setting following the discharge from the hospital …”
Section: Discussionmentioning
confidence: 99%
“…25 Several studies from Europe and Australia have confirmed a marked reduction of in-hospital mortality among patients with cirrhosis, but without assessment of mortality rates in the outpatient setting following the discharge from the hospital. [26][27][28] The strengths of our study are the utilization of a nationwide database. Our study represents outcomes of a large population of hospitalized patients with ESLD over a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, liver cirrhosis (LC) and hepatocellular carcinoma (HCC) are the two main causes of death due to liver diseases. These two serious conditions caused, according to the last available data, 8071 deaths from LC and 10,116 from HCC [1]. Several Italian studies over the years have shown that, at least in 65% of cases, these two diseases are linked to HCV chronic infection [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…1 Hepatocellular carcinoma (HCC) is the predominant primary liver cancer in many countries, and HCC-related mortality continues to increase. [2][3][4] The computed tomography (CT) and magnetic resonance imaging (MRI) characteristics of HCC are well described, and the diagnostic algorithm for HCC [Liver reporting and data system (LI-RADS)], which is based on CT, MRI with extracellular contrast material, or MRI with hepatobiliary contrast material (namely, gadoxetate disodium, also known by the trade name Primovist or Eovist), has been established. 5,6 Gadoxetate disodium is a liver-specific contrast material that allows both dynamic study and hepatocyte imaging at the hepatobiliary phase (HBP).…”
Section: Introductionmentioning
confidence: 99%